2005
DOI: 10.1016/j.rmed.2005.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Exercise testing determines survival in patients with diffuse parenchymal lung disease evaluated for lung transplantation

Abstract: Cardiopulmonary exercise test parameters and the 6MWTD were associated with the risk of death. Measures during exercise may be useful for determination of prognosis and for prioritizing patients with diffuse parenchymal lung disease for lung transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 29 publications
6
77
1
1
Order By: Relevance
“…This finding differs from previous studies (6,23) and likely reflects differences in walk protocols. In the current study, patients were tested without supplemental oxygen, and the walk was halted if Sa O 2 decreased to 86%.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding differs from previous studies (6,23) and likely reflects differences in walk protocols. In the current study, patients were tested without supplemental oxygen, and the walk was halted if Sa O 2 decreased to 86%.…”
Section: Discussioncontrasting
confidence: 99%
“…Our data highlight that even mild desaturation is a risk factor for subsequent mortality. Previous studies demonstrate that desaturation during a 6MWT is associated with increased risk of subsequent mortality when evaluated as a continuous variable (6,23) or using a threshold of р 88% (4, 7). Furthermore, the latter threshold was noted to be a reproducible parameter during short-term testing (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike many other studies [1,33,34], this retrospective analysis focused on IPF patients affected by milder disease (mean FVC 70.2%, and mean DLCO 47.9%) [32]. The study demonstrated the importance of the initial evaluation of PH and supported previous observations indicating that PH is not just a result of restrictive impairment in patients with IPF [1,20,35]. In the study by KIMURA et al [32], higher mean PAP was an independent prognostic factor, comparable to FVC % predicted, a well-known prognostic indicator in IPF.…”
Section: Prognostic Significance Of Ph In Ipfsupporting
confidence: 70%
“…It is believed that a reduction of DL,CO level below 50% of the predicted value is an important indication for the initiation of therapeutic intervention. Cardiopulmonary exercise testing and 6-min walk distance are also important for the evaluation of the functional status of SSc patients [24], they can identify factors limiting exercise [70,71], evaluate the effect of pharmacological or nonpharmacological interventions [72] and predict survival [73]. However, they do not lack cardinal limitations.…”
Section: Clinical and Laboratory Featuresmentioning
confidence: 99%